Comparison of a gelatin particle agglutination test and enzyme-linked immunosorbent assay for detection of antibody to m. leprae - Qian, Lishi (1992)
Two rapid diagnostic methods, Enzyme-linked Immunosorbant Assay (ELISA) and the Gelatin Particle Agglutination Test (GPAT), have been developed recently for epidemiological monitoring of the efficacy of chemotherapy and post-treatment follow-up of patients. Both these tests make use of semisynthetic of the phenolic-glycolipid-l, the specific antigen of M. leprae, but differ in methodology. This report examined the 2 tests with 1059 sera collected at an endemic area in Manila, Philippines. ELISA and GPAT were compared in terms of the seropositivity, the concordant rates, the sensivity and specificity in 305 Multibacillary (MB), 179 Paucibacillary (PB), 38 Household Contacts (HC), 126 school children in High Risk area (HR), 211 Normal Blood donors (NB) and 200 Normal Students (NS). The Gelatin Particle Agglutination Test (GPAT) was found to be much simpler and easier to perform and generally more sensitive but less specific compared with ELISA the sensivity of GPAT in MB patients (83.04 ) group was much higher than those in PB patient (41.86 ). The concordants rates, ranged from 87 in normal populations and 57.89 in household contacts. Chi-square test of homogeneity indicated that the concordant rate between ELISA and GPAT in normal populations was significantly higher than that in patients and contacts populations. The concordant rate of MB untreated decreased after being treated by multi-drug therapy 6 months or longer. The seropositivity of GPAT was higher than that of ELISA in all study population except the household contacts. The seroposivility of both GPAT and ELISA in MB were higher than the seropositivity of these 2 tests in PB patients. In conclusion, this study suggested that the GPAT is a sensitive but less specific test compared with ELISA. However, it is easy to perform and inexpensive. Therefore, it can be considered as a screening test for detection of the M. leprae infection, especially of the multibacillary type.
Thesis (Master of Science in Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Enzyme-linked immunosorbent assay; Immunoenzyme technique; Gelatin particle agglutination test; Leprosy